Mediating Role of Self Esteem in Gullibility (Unsuspecting)and Emotional Self Disclosure (Anxiety and Fear)Among Institutionalized Orphans (Journal of Asian Development Studies, 2024)
The present study investigated the relationship of gullibility, self-esteem and emotional selfdisclosure (ESD) among institutionalized orphans. This study aimed to examine the mediatingrole of self-esteem in gullibility(unsuspecting) and emotional self-disclosure (anxiety, fear). Inaddition, the mediating role of self-esteem was explored. A sample of 100 orphans (50 boys,50 girls) were selected through a purposive sampling strategy, aged 12-18 years (M=15.29,SD=1.68) from four orphanages in Lahore. The research instruments used were The gullibilityscale (Alessandra, 2016), the Rosenberg self-esteem scale (Rosenberg, 1965) and theEmotional self-disclosure scale (Snell et al., 2013). Results revealed a significant negativerelationship between gullibility and self-esteem. Moreover, a significant positive relationshipwas found between gullibility and emotional self-disclosure. Results also revealed a significantnegative relationship between self-esteem and emotional self-disclosure (depression, anxietyand fear). The mediation analysis showed that the relationship betweengullibility(unsuspecting) and emotional self-disclosure (anxiety and fear) amonginstitutionalized orphans was significantly mediated by self-esteem. Therefore, further studiesare needed to investigate and understand their level of gullibility and to promote quality forthis vulnerable group of adolescents closely. Such findings will facilitate an understanding ofthe psychological health problems faced by adolescent orphans residing in orphanages.